Review Article On Sandhan Kalpana In Ayurveda - Jatoliya, Vijay Kumar; Shukla, Govind Sahay; Agarwal, Rajaram; Goyal , Manisha (International Research Journal of Ayurveda & Yoga, 2021)
Ayurveda is a traditional system of medicine. Ayurveda therapies have varied and evolve over more than two millennia. In the Ayurveda therapy includes medicines, special diets, meditation, yoga, massage, laxatives, enemas and medical oils etc. It is based on the belief that health and mitigation depend on a balance between mind, body, and spirit. In Ayurveda, compilation of traditional ancient Indian medicine practice is called Rasashastra, which detail processes by various metals, minerals and other substances including mercury. Rasashastra is a pharmaceuticals branch of Indian system of medicine which mainly deal with metals, minerals, animal origin product, toxic herbs and their uses in therapeutics. Rasashastra & Bhaishajya Kalpana is an important branch of Ayurveda. Preparation of medicine is performed in this. In Ayurveda many types of formulation are applied to cure the diseases. Herbal and mineral preparation are used as single or combined forms to treat the disease. In Ayurveda literature, Sharangadhar Samhita highlighted the concept of the formulation. Sandhan Kalpana (biomedical fermented formulations) is an important formulation. It is used in the cure of many types of disease and health promotion. All preparation which is resulting from the fermentation procedure is included in Sandhan Kalpana. Sandhan is the process of fermentation where the liquid substance (Kwath, Swarasa, and other liquid preparation), sweetening agent (jaggery, honey, sugar), praksepa dravya (fine powder of medicinal drug), Sandhan dravya (fermentation agents) (Dhakti Pushpa, Madhuka pushpa as fermentation initiators) are put together in the mud pot or inert vessel and it is kept for a specific period to facilitate the process of fermentation.